1984
DOI: 10.1111/j.1432-1033.1984.tb08236.x
|View full text |Cite
|
Sign up to set email alerts
|

The multiple phosphorylation of the microtubule-associated protein MAP2 controls the MAP2: tubulin interaction

Abstract: Pre-phosphorylation of the microtubule-associated protein MAP2 with the co-purifying CAMP-independent protein kinase (a) decrease the affinity of MAP2 for taxol-stabilised microtubules, (b) increases the dissociation rate constant for microtubule polymerisation, each of which is dependent upon the level of phosphorylation, but (c) has no effect on the association rate constant. Microtubule assembly has no effect on the kinetics of phosphorylation, whereas phosphorylation of pre-assembled microtubules causes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(76 citation statements)
references
References 24 publications
3
73
0
Order By: Relevance
“…Taxanes block tubulin depolymerisation, resulting in impairment of cellular mitosis (Horwitz, 1994), generating nuclear abnormalities and multipolar divisions, ultimately leading to cell death (Abal et al, 2003). Taxane-induced tubulin alterations may also affect microtubule-associated proteins (MAPS) (Burns et al, 1984, Haycock et al, 1992, potentially leading to multiple cellular dysfunctions. Microtubule-associated proteins are among the protein clients of heat-shock proteins (HSP70 and HSP90), themselves associated with and stabilising numerous proteins such as HER2, AKT and the AR (Georget et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Taxanes block tubulin depolymerisation, resulting in impairment of cellular mitosis (Horwitz, 1994), generating nuclear abnormalities and multipolar divisions, ultimately leading to cell death (Abal et al, 2003). Taxane-induced tubulin alterations may also affect microtubule-associated proteins (MAPS) (Burns et al, 1984, Haycock et al, 1992, potentially leading to multiple cellular dysfunctions. Microtubule-associated proteins are among the protein clients of heat-shock proteins (HSP70 and HSP90), themselves associated with and stabilising numerous proteins such as HER2, AKT and the AR (Georget et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…For the microtubul¢-assoeiated protein 2 (MAP 2), it has been shown that phosphorylation by a co-purifying cyclic AMP-independent kinase reduces its affinity to mierotubules [25]. Conversely, phosphorylation by calmodulin-dependent kinase reversibly renders tubulin incapable of assembly and binding to microtubule-associated proteins [18].…”
Section: Discussignmentioning
confidence: 99%
“…MAPs isolated from tissue or cells are phosphoproteins (Sloboda et al, 1975;Vallee, 1980;Burns et al, 1984;Tsuyama et al, 1986;Brugg and Matus, 1991;Watanabe et al, 1993), MAPs are good substrates for many protein kinases in vitro (Theurkauf and Vallee, 1983;Lindwall and Cole, 1984;Mori et al, 1991;Drewes et al, 1992), and phosphorylation interferes with their microtubule stabilizing capacity (Brugg and Matus, 1991;Shiina et al, 1992;Drechsel et al, 1992;Biernat et al, 1993;Brandt et al, 1994;Ookata et al, 1995;Trinczek et al, 1995). In the case of tau protein, phosphorylation has been extensively studied, because aberrantly phosphorylated tau is involved in the neurofibrillar pathology of Alzheimer's disease (reviewed by Goedert (1993), Mandelkow and Mandelkow (1993), and Trojanowski and Lee (1994)).…”
mentioning
confidence: 99%